Multi-Omics Approaches to Biomarker Discovery: Integration of Genomics, Proteomics, And Metabolomics for Precision Medicine - A Comprehensive Review - Thapa, Sandeep; Khanal, Santosh; Joshi, Govardhan; Bhattarai, Dilip (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
The advent of high-throughput molecular profiling technologies has revolutionized biomedical research, allowing scientists to explore complex biological systems at multiple levels: genomic, proteomic, and metabolomic. These combined "multi-omics" approaches are proving instrumental in identifying reliable biomarkers essential for the success of precision medicine. This review explores the current landscape of multi-omics integration, from technological advances to computational frameworks, and delves into their real-world applications in disease diagnostics and prognostics. We discuss how integrating diverse datasets enhances clinical insights and outline the challenges in standardization, data harmonization, and clinical translation. Emerging tools, including artificial intelligence, are highlighted for their potential to manage complexity and propel discoveries from the lab to the clinic.